Patents and technological change: A review with focus on the FEPOCI database - Tuomo Nikulainen; Mika Pajarinen; Christopher Palmberg (The Research Institute of the Finnish Economy (ETLA), 2005)
Technological change and innovation is driven by the generation and accumulation of new knowledge. However, these processes are elusive from an empirical viewpoint and economists have put a lot of effort into identifying and developing appropriate indicators to measure knowledge and its development. The purpose of this paper is to provide insights into the use of patents as a generally accepted indicator of new knowledge and intermediate outputs of innovative activity more generally. It is intended as a background paper for further analysis based on the new, so-called FEPOCI, database on Finnish patents and related citations granted at the European Patent Office (EPO) from the years 1991-2004. We discuss the patent system and its general characteristics, identify patents as indicators of new knowledge and innovative activities, briefly review previous research using patent data, and introduce the FEPOCI database through presenting the search criteria used for the data retrieval, the included variables, and some basic descriptive statistics of the data for validation purposes.
Keywords: 330; Patents; citations; innovation; technological change; Finland; Patent; Technischer Fortschritt; Finnland